IMPLEMENTATION OF EDUCATIONAL MANAGEMENT INFORMATION SYSTEM (SIM-ISLAMIC EDUCATION) IN MADRASAH ADMINISTRATIVE EFFICIENCY - Khafidah, Wahyu; Akyuni, Qurrata; Zulfadli (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
This study analyzes the implementation of an Islamic Education Management Information System (ISMS) to improve madrasah administrative efficiency in the era of digital transformation. Using a Systematic Literature Review approach to ten selected journal articles from various trusted academic databases for the 2023-2025 period, this study reveals that digitizing madrasah administration through an ISMS has a significant impact on increasing operational efficiency. The systematic implementation process through the stages of initiation, elaboration, development, and transition showed a product suitability level of 90.29% based on expert validation. The artificial intelligence -based system achieved 95% accuracy in multimodal data processing, surpassing conventional systems which only achieved 80%. The system's effectiveness is proven by reducing administrative burdens, accelerating data processing, increasing information accuracy, and facilitating data-driven decision-making. Supporting factors for success include leadership commitment, adequate digital infrastructure, and human resource readiness. Key challenges faced include the digital divide, limited infrastructure, technophobia , poor internet connectivity, and budget constraints. This study recommends the development of a comprehensive digitalization roadmap , strengthening human resource capacity through ongoing training, and developing a contextual system effectiveness evaluation model to optimize digital transformation in sustainable Islamic education governance